Pharmacological differences between memory consolidation of habituation to an open field and inhibitory avoidance learning - Vianna,M.R.M. (2001)
Rats implanted bilaterally with cannulae in the CA1 region of the dorsal hippocampus or the entorhinal cortex were submitted to either a one-trial inhibitory avoidance task, or to 5 min of habituation to an open field. Immediately after training, they received intrahippocampal or intraentorhinal 0.5-µl infusions of saline, of a vehicle (2% dimethylsulfoxide in saline), of the glutamatergic N-methyl-D-aspartate (NMDA) receptor antagonist 2-amino-5-phosphono pentanoic acid (AP5), of the protein kinase A inhibitor Rp-cAMPs (0.5 µg/side), of the calcium-calmodulin protein kinase II inhibitor KN-62, of the dopaminergic D1 antagonist SCH23390, or of the mitogen-activated protein kinase kinase inhibitor PD098059. Animals were tested in each task 24 h after training. Intrahippocampal KN-62 was amnestic for habituation; none of the other treatments had any effect on the retention of this task. In contrast, all of them strongly affected memory of the avoidance task. Intrahippocampal Rp-cAMPs, KN-62 and AP5, and intraentorhinal Rp-cAMPs, KN-62, PD098059 and SCH23390 caused retrograde amnesia. In view of the known actions of the treatments used, the present findings point to important biochemical differences in memory consolidation processes of the two tasks.